Multiple Chronic Diseases Associated With Tooth Loss Among the US Adult Population - Zhang, Yuqing; Leveille, Suzanne G.; Shi, Ling (Frontiers in Big Data, 2022)
Background: Half of US adults aged 20-64 years have lost at least one permanent tooth; one in six adults aged 65 and over in the U.S. are edentulous. Tooth loss and edentulism interfere with nutritional intake and quality of life. Although selected chronic diseases (e.g., diabetes) have been identified as possible risk factors for tooth loss, data on multiple chronic diseases and on having two or more concurrent chronic diseases (multimorbidity) in relation to tooth loss is lacking. This study aimed to assess the association among multiple chronic diseases, multimorbidity, and tooth loss in US adults. Methods: We performed a secondary data analysis using the US 2012 Behavioral Risk Factor Surveillance System (BRFSS), a national cross-sectional telephone survey studying health conditions and health behaviors among US adult non-institutionalized residents. Descriptive analysis and multinomial logistic regressions were used to examine the relationship between several chronic diseases and tooth loss, and between multimorbidity and tooth loss. Results: Among the sample (N=471,107, mean age 55 years, 60% female), the chronic diseases that were associated with edentulism were: chronic obstructive pulmonary disease [Adjusted Risk Ratio (Adj. RR) 2.18, 95%CI 2.08-2.29]; diabetes (Adj. RR 1.49, 95%CI 1.44-1.56) arthritis (Adj. RR 1.49, 95%CI 1.44-1.54); cardiovascular disease (Adj. RR 1.38, 95%CI 1.30-1.45); stroke (Adj. RR 1.31, 95%CI 1.24-1.40); kidney disease (Adj. RR 1.16, 95%CI 1.08-1.25); cancer (Adj. RR 1.05, 95%CI 1.01-1.11); asthma (Adj. RR 1.07, 95%CI 1.02-1.12). For those reporting having 1 to 5 and reporting 6 or more teeth lost, the association remained significant for most of included diseases albeit the magnitude of association appeared to be smaller. Also, adults with multimorbidity were more likely to have tooth loss (lost 1-5 teeth: Adj. RR 1.17, 95% CI 1.14-1.19; lost≥6 teeth: Adj. RR 1.78, 95%CI 1.73-1.82; edentulous: Adj. RR 2.03, 95%CI 1.96-2.10). Conclusions: Multiple chronic diseases were associated with edentulism and tooth loss. Multimorbidity associationed with higher risk of tooth loss. Findings from this study will help identify populations with increased risk for oral problems and nutritional deficits, thus assessment of oral health should be evaluated further as an important component of chronic illness care.